Enrichment of the rotifer Brachionus plicatilis fed an Antarctic bacterium containing polyunsaturated fatty acids - David Nichols; Hart, PR; Peter Nichols; Thomas McMeekin (1996)
The Antarctic bacterium, strain ACAM 456, is known to produce eicosapentaenoic acid (20:5n-3, EPA). Following growth in batch culture, suspensions of this bacterium, at initial concentrations of 107, 108 and 109 cells ml-1, were used as foods for three respective cultures of the rotifer Brachionus plicatilis. At 6 and 24 h. rotifers were removed, harvested and extracted for analysis of fatty acid composition, which was compared to that of rotifers grown on baker's yeast. Incorporation of EPA, along with bacterial fatty acid markets (i13:0, i15:0 and 14:0), was evidenced at all bacterial food concentrations tested. The highest observed incorporation occurred when rotifers were grown in the medium initially containing 109 bacteria ml-1. After 24 h of feeding, the level of EPA reached 9.4% of total fatty acids in the fed rotifers (6.7 ng of EPA rotifer-1). ACAM 456, a bacterial strain with the ability to produce EPA, was therefore shown to be a potential alternative enrichment food for the rotifer Brachionus plicatilis under feeding conditions that may be applicable to many Australian mariculture operations.